The Rescuers: intersections of individual and group activism and the recognition of the human-animal “Link” - Button, Andrea (Kansas State University, 2015)
Academics, victims, and advocates have increasingly brought attention to the need for programs and policies to protect and shelter nonhuman victims of domestic violence. Research focused on the “Link” between human-based violence and violence against animals has played a significant role in the creation of these programs, and has prompted a more holistic approach to providing services to all victimized family members. In this dissertation, I focus on the unique origin points of several animal-friendly domestic violence organizations and the models used to serve both human and nonhuman victims, as well as on the individual advocacy and activism of animal-friendly domestic violence organization workers. Data collection from semi-structured interviews with thirty domestic violence workers and advocates provides the foundation for my investigation of the importance of community networks and individual identity as a source of professional navigation of the connected spheres of domestic violence and animal abuse. This study extends the ever-growing collection of research on the “Link” and on the broader discipline of human-animal studies. Finally, this research provides an additional perspective on the use of personal and collective identity to engage in advocacy on behalf of nonhuman victims of domestic violence.
Keywords: animal abuse; human-animal interactions; identity; social movementsdomestic violence; Sociology (0626)